The role of inflammation in autoimmune disease: a therapeutic target - Xiang, Yu; Zhang, Mingxue; Jiang, Die; Su, Qian; Shi, Jianyou (Frontiers in Immunology, 2023)
Autoimmune diseases (AIDs) are immune disorders whose incidence and prevalence are increasing year by year. AIDs are produced by the immune system's misidentification of self-antigens, seemingly caused by excessive immune function, but in fact they are the result of reduced accuracy due to the decline in immune system function, which cannot clearly identify foreign invaders and self-antigens, thus issuing false attacks, and eventually leading to disease. The occurrence of AIDs is often accompanied by the emergence of inflammation, and inflammatory mediators (inflammatory factors, inflammasomes) play an important role in the pathogenesis of AIDs, which mediate the immune process by affecting innate cells (such as macrophages) and adaptive cells (such as T cells and B downdial), and ultimately promote the occurrence of autoimmune responses, so anti-inflammatory agents are one of the treatment strategies of AIDs. This review will briefly describe the role of inflammation in the pathogenesis of different AIDs, and give a rough introduction to inhibitors targeting inflammatory factors, hoping to have reference significance for subsequent treatment options for AIDs.